UNICEF And Its Role In Children Safeguarding In Disasters And Armed Conflicts Situations - دندش, دينا (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Children are considered the most affected group by the conditions and events that their societies are exposed to, whether these conditions are caused by nature, such as natural disasters like earthquakes and hurricanes, or from human act such as wars and armed conflicts, and the children crying sounds awakened the conscience of humanity and promoted it to make urgent efforts to stop their suffering, preserve their lives and enhance their capabilities, as they are the cornerstone for building societies and their development, and the owners of the future role in realizing humanity's dream of peace and prosperity. With the beginning of the emergence of modern international organization, it was necessary to allocate one of them to work to preserve the rights of children all over the world. UNICEF has emerged to play this role, as humanitarian work related to children that is at the core of its mandate, and its global humanitarian structure supports its work in all emergency circumstances, including disasters and armed conflicts, in addition to natural conditions, and enables it to perform its tasks in securing the basic rights of children wherever they are.